Gramsci and hegemonic struggle in a globalized world - Muhr, T. (The Elgar companion to Antonio Gramsci, 2024)
This chapter establishes dialogue between Gramsci and decolonial thought, identifying Gramsci as an anti-colonial and decolonial Global Southerner. By reference to Gramsci’s (1971, p. 240) adage that ‘the line of development is towards internationalism, but the point of departure is “national”’, the chapter discusses the ALBA-TCP/ALBA Movements ‘pluri-scalar war of position’, which operates across subnational, national, international, transnational and supranational geographical scales in global counter-hegemonic struggle. Following the pluri-scalar war of position’s empirical grounding, the chapter explores Gramsci’s thinking in Our American political praxis, particularly el pueblo (the people) as the collective historical revolutionary subject. The conclusion argues for imagining a counter-hegemonic historical bloc as a Global South bloc, while eliciting structural constraints to its construction. The chapter is of relevance to both political and social forces seeking decolonial, anti-capitalist transformation, including governments, political parties, and local/national as well as global movements such as the Progressive International.